Exploring The Student Experience Using The Career Tree to Choose an Advanced School (Case Study at SMP Negeri 2 Bululawang) - Anggraini, Andini Yuliana; Firdaus, Krisnaldy; Maulidya, Nabila; Apriani, Rizka; Ekawati, Fitri (Universitas Negeri Malang, 2024)
This study was conducted to explore students' experiences of using career trees to choose a school. This research is qualitative research with a case study research type. Data sources in this study include primary data obtained through in-depth interviews, participatory observation, and documentation, as well as secondary data taken from relevant documents or literature. The population in this study were all grade 8 students totaling around 225 people. The technique used was a purposive sampling technique. The sample consisted of three grade 8 students who actively participated in making career trees and one counseling teacher. Data collection methods applied in this study include interviews, observation, and documentation techniques. Data obtained from interviews and observations were organized into main themes that emerged using thematic analysis. The type of triangulation used was method triangulation. The results showed that there were significant changes in the exploration of students' experiences of using career trees to choose schools after graduating from junior high school. Students were able to increase students' understanding of career choices, the impact of using career trees, and the challenges faced when working on career trees. Keywords: Exploration; Experience; Various Majors; Career Tree